Union Minière du Haut-Katanga 1906-1956 (Bruxelles : L. Cuypers, 1956)
Bibliotheek Camille Huysmans
Exemplaar gedrukt voor Camille Huysmans
Frans
Monografie
Keywords: mijnbouwindustrie; Belgisch Congo